(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Functional fibrous materials are a new family of fibre materials whose physical and chemical properties are sensitive to the change in the environment such as temperature, pressure, electric field, magnetic field, optical wavelength, adsorbed gas molecules and the pH value. This paper introduces a new approach to translate functions from nanoparticles to fibrous structures by co-electrospinning. Examples of nanofibres that have tailorable mechanical, electrical, magnetic, optical, thermal, hygroscopic, and antimicrobial functions are shown. The paper concludes with an example of the development of a multifunctional nanofibre scaffold for cartilage tissue regeneration.